On the Stability of Biquadratic-Bilinear Velocity-Pressure Finite Elements (Journal of Computational Mathematics, 1992)
In this paper, the stability of biquadratic-bilinear velocity-pressure finite elements are discussed for the stationary Stokes problem. It is proved that there exist constants $c ,c' ＞0$ independent of $h$ such that Hence a question in [1] is answered.